The POST trial: initial post-market experience of the Penumbra system: revascularization of large vessel occlusion in acute ischemic stroke in the United States and Europe - Tarr, Robert; Hsu, Dan; Kulcsar, Zsolt; Bonvin, Christophe; Rufenacht, Daniel; Alfke, Karsten; Stingele, Robert; Jansen, Olav; Frei, Donald; Bellon, Richard; Madison, Michael; Struffert, Tobias; et al. (Journal of Neurointerventional Surgery, 2018)
BACKGROUND AND PURPOSE: The purpose of this study was to assess the initial post-market experience of the device and how it is compared with the Penumbra Pivotal trial used to support the 510k application. METHODS: A retrospective case review of 157 consecutive patients treated with the Penumbra system at seven international centers was performed. Primary endpoints were revascularization of the target vessel (TIMI score of 2 or 3), good functional outcome as defined by a modified Rankin scale (mRS) score of ≤2 and incidence of procedural serious adverse events. Results were compared with those of the Penumbra pivotal trial. RESULTS: A total of 157 vessels were treated. Mean baseline values at enrollment were: age 65 years, NIHSS score 16. After use of the Penumbra system, 87% of the treated vessels were revascularized to TIMI 2 (54%) or 3 (33%) as compared with 82% reported in the Pivotal trial. Nine procedural serious adverse events were reported in 157 patients (5.7%). All-cause mortality was 20% (32/157), and 41% had a mRS of ≤2 at 90-day follow-up as compared with only 25% in the Pivotal trial. Patients who were successfully revascularized by the Penumbra system had significantly better outcomes than those who were not. CONCLUSION: Initial post-market experience of the Penumbra system revealed that the revascularization rate and safety profile of the device are comparable to those reported in the Pivotal trial. However, the proportion of patients who had good functional outcome was higher than expected.
EVALuna2:34914